The Role of Transabdominal Ultrasound in Office Urology - Keong Tatt Foo FRCS (ed), FAMS (Urology) (Proceedings of Singapore Healthcare, 2013)
Ultrasound diagnosis was introduced in the 1970s, and rapidly became popular in the outpatient clinic because of its safety and non-invasiveness. In Urology, the transabdominal ultrasound (TAUS) is useful to assess patients with lower urinary tract symptoms, to diagnose benign prostatic hyperplasia, and to classify its severity. TAUS is also used in diagnosing stones in patients with loin pain and urinary infections. Micro and gross haematuria are common problems seen in the clinic and TAUS can help in the early diagnosis of bladder tumours. Hydronephrosis from obstructive uropathy and scrotal ultrasound for hydrocele and tumour can be easily seen. However, for more details in diagnosing kidney tumours and testicular torsion, patients need to be referred to the Radiological Department for further assessment. TAUS is useful in the clinic for diagnosing our patients early and helping in further assessment in the clinic. It is also cost effective in improving patient care.